Two printed copies of a letter from John E. Milholland to the editor of 'The Nation' published as an advertisement in the newspaper, - Milholland, John E., 1860-1925 (1920)
Letter praises the Committee of One Hundred which has been organised by 'The Nation' newspaper for investigation of atrocities in Ireland, and suggests that 'The Nation' "should invite general public subscriptions for the expenses of the Commission which is to conduct the investigation."